Challenges Facing Soes and Soe Subsidiaries Toward Business Tranformation Law Enforcement and Human Rights Protection (Post Constitutional Court Decision Number 01/PHPU-PRES/XVII/2019) - Binsar Jon Vic S (Warmadewa Press, 2023)
Business transformation, law enforcement and human rights protection are strategic and or universal issues that applies to countries and nations in the world including and in particular become a challenge and dilemma for SOEs and or SOE’s Subsidiaries. The research aims to know how do State-Owned Enterprises/SOE subsidiaries anticipate and business transformation the threat of corporate criminal acts related to law enforcement and human rights protection and to know business transformation law enforcement officers and relevant institutions anticipate post Decision of the Constitutional Court Number 01/PHPU-PRES/XVII 2019 towards SOEs/SOES subsidiaries. The method used of this research is normative juridical legal research. The result shows that SOEs/SOE subsidiaries have a central role in supporting for business transformation and law enforcement and protection of human rights both internal and external matters of the corporation. Post Constitutional Court’s Decision Number 01/PHPU-PRES/XVII/2019 becomes a legal source that can inspire Law Enforcement Officials and related institutions/agencies to make appropriate adjustments to laws and regulations governing SOEs and or SOE subsidiaries.